2010
DOI: 10.1021/bi100631f
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Association Facilitates Degradation and Cleavage of the Cyclin-Dependent Kinase 5 Activators p35 and p39

Abstract: Cyclin-dependent kinase 5 (Cdk5) is activated by binding to its activators, p35 and p39. The level of Cdk5 activity is determined by the amount of p35 and p39, which is regulated not only by transcription but also via proteasomal degradation. Alternatively, calpain-induced cleavage of p35 to p25 can induce aberrant Cdk5 activation. As the regulation of p35 and p39 proteolysis is not well understood, we have studied here the mechanisms governing their degradation and cleavage. We find that p35 and p39 undergo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 53 publications
(119 reference statements)
1
51
0
Order By: Relevance
“…In the present study, we demonstrate aberrant redox regulation of Cdk5 activity by S-nitrosylation in AD models and in human brain. NOS1 and Cdk5 are both localized at the cell surface (45,46), and the close proximity of NOS1 to Cdk5 may thus make endogenous NO available for reaction to form SNO-Cdk5. We found that S-nitrosylation increases Cdk5 kinase activity, identified the cysteine residues susceptible to (patho)physiological regulation by .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrate aberrant redox regulation of Cdk5 activity by S-nitrosylation in AD models and in human brain. NOS1 and Cdk5 are both localized at the cell surface (45,46), and the close proximity of NOS1 to Cdk5 may thus make endogenous NO available for reaction to form SNO-Cdk5. We found that S-nitrosylation increases Cdk5 kinase activity, identified the cysteine residues susceptible to (patho)physiological regulation by .…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid Construction-pCMV5-mouse Cdk5, pCMV2-FLAG-mouse Cdk5, pCMV5-kinase-negative (kn) Cdk5 D144N, pCMV5-mouse p35, pcDNA3-mouse p35-myc, pcDNA3-mouse p25-myc, pCAGGS-GFP, pCAGGS-DsRed, pCMV5-FLAG-p39 activation domain (AD), and pCMV2-FLAG-Cyclin I have been described previously (21)(22)(23)(24)(25)(26)(27). pME-Fyn, constitutively active (ca) pME-Fyn Y531F, kinasenegative pME-Fyn K299M, and pcDNA-caSrc Y530F were provided by T. Tezuka and T. Yamamoto at the University of Tokyo (28).…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that the activation of Cdk5 is due to the increased p35 but not Tyr-15 phosphorylation, at least in the cell culture overexpression system. p35 is a protein with a short half-life (24,34). To ask how Fyn increases p35 protein, we measured the synthesis and degradation of p35 in the presence of MG132 proteasome inhibitor and cycloheximide protein synthesis inhibitor, respectively.…”
Section: Coexpression Of Cdk5 Activators Suppresses Tyr-15mentioning
confidence: 99%
“…Similar to p35, p39 possesses a N-terminal myristoylation site, although p39 has a longer half-life than p35 (Minegishi et al, 2010). p39 is also cleaved by calpain to yield p10 and p29 under neurotoxic conditions (Patzke and Tsai, 2002).…”
Section: Introductionmentioning
confidence: 99%